Bibliotekarerne - en profession der former og formes af et aktør-netværk - Schreiber, Trine (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
Using actor network theory (ANT) as a starting point, the aim of the paper is to describe relationships between heterogenous actors in a particular kind of library work and to discuss how these relationships might potentially be part of a preliminary actor-network representing a profession of librarianship. The particular kind of library work involved in the discussion is user teaching and -guidance in libraries affiliated with educational institutions. The paper draws on this particular kind of work to illustrate the use of ANT in a discussion about the profession of librarianship. The data collection procedure has been guided by ethnographic methodology considerations. As an actor-network, a profession is not a static entity organised around fixed connections. It is undergoing shifts in character as new actors or relations are forged and old ones wear out. Regarding the particular kind of library work, the paper has a focus on actors such as librarians, teachers, students, digital technologies, and political paradigms of control. The author examines how librarians in the particular kind of library work create and maintain relationships with teachers and students. The paper provides a description of the ways influential actors such as digital technologies and political paradigms of control intervene in these processes. The paper concludes that through these relationships, new areas of work and new understandings of professions are under way to be established. These processes might lead to an actor-network intertwined with those many other actor-networks that librarians in general are involved in because of other practices and relationships.